PERAN ORANG TUA DALAM MENGAWASI PENGGUNAAAN GADGET TERHADAP REMAJA USIA 13-15 TAHUN - Tarigan, Thomas Natalisa; Tibo, Paulinus; Lumbanbatu, Claudia (STP St. Bonaventura Medan, 2022)
Researchers aim to determine the role of parents in supervising the use of gadgets among teenagers aged 13-15 years in the Good Shepherd Parish of Lubuk Pakam. This research is motivated by facts in the field that the role of parents is only to fulfill all the needs of teenagers but they are less aware that monitoring the use of gadgets for teenagers is not running optimally. The research method used is a qualitative research method. Based on qualitative research, the determination of informants was carried out using purposive sampling and snowball sampling. The findings of this research use data collection techniques including interview, observation and documentation techniques. The place where the researcher conducted the research was the Good Shepherd Parish, Lubuk Pakam. The findings of this research show that the role of parents in monitoring the use of gadgets has not been fully implemented. And the results of research regarding the reasons parents give gadgets to teenagers, involving teenagers to think critically in using gadgets, parents limiting the time they use gadgets and what are the positive and negative impacts of using gadgets on teenagers aged 13-15 years